Penelitian Wisata Susur Sungai dengan Konsep Ekowisata - Khaerunnisa Nurul K.; Slamet Trisutomo; Sri Aliah Ekawati (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2017)
Recognizing the diverse functions of the river, several regulations have been established to support water development, utilization or utilization activities through the administration, supply, use, development, and exploitation of water resources (rivers) with reference to the management of water resources determined in each region. So that the river can be planned for activities that are more beneficial than just being a fishing industry or a place for garbage and sewage disposal. This study aims to identify the potentials and problems in the Tallo River related to the tourism of the alongside the river, identify the characteristics of each region traversed by the Tallo River, and develop the planning concept for the Tallo River as a tourism area for the river along the ecotourism by using descriptive methods through a qualitative approach. The results of this study include the direction of the planning of the development of the riverside tourism with the concept of ecotourism including the design of the ship and its accommodation, accessibility or routes, supporting facilities, and activities; determine the facilities and infrastructure to support the river alignment tour then divide the zonation of the tourist attraction area based on the principle of ecotourism, namely conservation, education, culture and community empowerment, and determine the shipping route and voyage travel time.